Impact of preoperative serum albumin-globulin ratio on disease outcome after radical cystectomy for urothelial carcinoma of the bladder - Schuettfort, Victor M; D Andrea, David; Quhal, Fahad; Mostafaei, Hadi; Laukhtina, Ekaterina; Mori, Keiichiro; Sari Motlagh, Reza; Rink, Michael; Abufaraj, Mohammad; Karakiewicz, Pierre I; Luzzago, Stefano; Rouprêt, Morgan; et al. (Urologic oncology, 2021)
INTRODUCTION: The Albumin-Globulin Ratio (AGR; albumin/total protein - albumin) has been associated with oncological outcome in various malignancies. However, its role in urothelial carcinoma of the bladder (UCB) has not been clearly established. In this study, we assessed the association of preoperative AGR (pAGR) with survival in patients who underwent radical cystectomy (RC) for UCB. MATERIAL AND METHODS: We conducted a retrospective analysis of an established multicenter database of 4.335 patients who were treated with RC for UCB. The cohort was divided into 2 groups according to the pAGR status. Binominal logistic regression as well as uni- and multivariable Cox regression analyses were used. The predictive value of the models was assessed by calculating receiver operating characteristics curves and concordance-indices (C-Index). The additional clinical value was assessed using the decision curve analysis (DCA). RESULTS: Overall, 1.670 patients (38.5%) had a low pAGR. On multivariable logistic regression analyses, low pAGR was associated with an increased risk of ≥pT3 disease at RC (odds ratio [OR] 1.15, 95% confidence interval [CI] 1.01-1.31, P= 0.04). On multivariable Cox regression analyses, low pAGR remained associated with worse recurrence-free survival (RFS, HR 1.24, 95% CI 1.1-1.37, P< 0.001), cancer-specific survival (CSS, HR 1.23, 95% CI 1.1-1.38, P< 0.001) and overall survival (OS, HR 1.17, 95% CI 1.07-1.28, P< 0.001). The addition of pAGR to multiple prognostic models that were respectively fitted for clinical and postoperative variables did not improve the predictive accuracy. CONCLUSION: pAGR status is an independent predictor of ≥pT3 disease, therefore it could help identify patients who have a higher likelihood to benefit from neoadjuvant systemic therapy. While pAGR was independently associated with RFS, CSS, and OS, it did not improve the predictive accuracy and clinical value beyond obtained by information already available. The predictive value of this biomarker in the age of immunotherapy needs further evaluation.
Keywords: Preoperative Period; Biomarker; nádory močového měchýře; Bladder cancer; Transitional cell carcinoma; výsledek terapie; sérové globuliny; sérový albumin; karcinom z přechodných buněk; Cystectomy; NMIBC; Serum Albumin; předoperační období; Humans; Serum Globulins; Urinary Bladder Neoplasms; Carcinoma, Transitional Cell; AGR; Treatment Outcome; lidé; MIBC; cystektomie